2000
DOI: 10.1038/sj.onc.1203831
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect between NF-κB subunits and p53 protein for transcriptional activation of human p53 promoter

Abstract: The tumor suppressor p53 plays a pivotal role in the cellular response to DNA damage as it controls DNA repair, cell cycle arrest and apoptosis. We studied the autoregulation of human p53 gene transcription in colon cancer cell lines. Wild-type p53 has been shown to autoregulate its own transcription either positively or negatively and probably in a cell-type-speci®c manner. Indeed, a p53 binding site has been described in the human and murine p53 promoters, but a direct binding of wild-type p53 protein to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 48 publications
(44 reference statements)
7
27
0
Order By: Relevance
“…Recent work suggests the involvement of p53 promoter activation by NF-kB (Benoit et al, 2000) and the existence of a promoter element that is involved in basal p53 gene expression and the stress response (Noda et al, 2000). Thus, suppression of NF-kB in cancer cells may provide an additional target for prevention of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests the involvement of p53 promoter activation by NF-kB (Benoit et al, 2000) and the existence of a promoter element that is involved in basal p53 gene expression and the stress response (Noda et al, 2000). Thus, suppression of NF-kB in cancer cells may provide an additional target for prevention of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ryan et al (2000) reported that induction of p53 caused activation of NF-kappaB and that this phenomenon correlated with the ability of p53 to induce apoptosis (Ryan et al, 2000). We previously showed an additive effect between NF-kappaB subunits and p53 for the transcriptional activation of TP53 (Benoit et al, 2000). Bohuslav et al (2004) described that p53 expression stimulated the S6 ribosomal serine/threonine kinase (RSK1), which in turn phosphorylated and activated the p65/RelA subunit of NF-kappaB (Bohuslav et al, 2004).…”
Section: Mechanisms Of P53-nuclear Factor-kappab Cooperationmentioning
confidence: 99%
“…Compared to the vast information and knowledge available regarding the regulation of p53 protein expression and function (Wang and Friedman, 2000;Ito et al, 2001;Wang et al, 2001), there is only a small amount of literature on transcriptional regulation of the p53 gene (Balint and Reisman, 1996;Benoit et al, 2000;Mokdad-Gargouri et al, 2001). However, control of p53 gene expression at the transcriptional level has been shown to play important roles in mitogenic stimulation or factor induced di erentiation (Reich and Levine, 1984;Soini et al, 1992;).…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factors shown to positively regulate p53 transcription include c-myc (Kirch et al, 1999;Lee and Rho, 2000), NF-kB (Pei et al, 1999;Benoit et al, 2000), YY1/NF1 (Lee et al, 1998(Lee et al, , 1999Nayak and Das, 1999), Ap1 (Kirch et al, 1999), and the HoxA5 homeobox containing gene product (Raman et al, 2000). Members of the PAX family are the only mammalian nuclear proteins shown to repress p53 transcription through a binding site present in the ®rst non-coding exon (Stuart et al, 1995).…”
Section: Introductionmentioning
confidence: 99%